Synchronic presentation of breast ductal carcinoma and follicular lymphoma: a diagnostic challenge - Morosini, Priscila Nunes Silva; Sabóia, Murilo do Valle; Cavalcanti, Tereza; Rothert, Ágata; Cavalcanti, Marcela (Mastology, 2020)
Synchronic tumors are rare events, even more clinically presenting as a rational metastatic sequence: breast cancer followed by axillary lymph node involvement. In the present case, after mastectomy associated with axillary emptying in a postmenopausal patient, we identified in the pathological report the presence of breast disease: invasive ductal carcinoma. However, differently from what was expected by the clinical examination, axillary lymph node involvement was not due to a disease of mammary origin, but to non-Hodgkin’s lymphoma — a new primary. In the world literature, there are few similar reports, and it is still necessary to accumulate similar cases to be able to hypothesize a single causality between these two tumor subtypes or cause-consequence relationship between the two entities.